The Effect of Implementing the Problem-Based Learning Model on Science Learning Outcomes at SMP Negeri 13 Sigi Biromaru - Aulia, Aisyah; Lilies,; Ashari, Abdul; Shamdas, Gamar B. N.; Alibasyah, Lestari; Zainal, Syech (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the effect of implementing the Problem-Based Learning (PBL) model on eighth-grade students’ science learning outcomes. This study employed a quantitative quasi-experimental approach with a nonequivalent control group design. The sample consisted of 53 eighth-grade students who were assigned to an experimental class and a control class. The experimental class was taught using the PBL model, whereas the control class received conventional instruction. Data were collected using a multiple-choice test administered before and after the treatment as a pretest and posttest. The test was designed to measure students’ cognitive learning outcomes in science. The data were analyzed using an independent samples t-test after the initial abilities of the two groups were examined. The results indicated that the two groups had relatively equivalent initial abilities before the intervention. After the treatment, the experimental class achieved a higher posttest mean score than the control class, and the difference between the groups was statistically significant. These findings suggest that PBL is more effective than conventional instruction in improving students’ science learning outcomes.